Abnormal cell surface antigen expression in individuals with variant CD45 splicing and histiocytosis. - Boxall, S; McCormick, J; Beverley, P; Strobel, S; De Filippi, P; Dawes, R; Klersy, C; Clementi, R; De Juli, E; Ferster, A; Wallace, D; Aricò, M; et al. (2004)
Hemophagocytic lymphohistiocytosis (HLH) and Langerhans cell histiocytosis (LCH) are members of a group of rare heterogenous disorders, the histiocytoses, characterized by uncontrolled accumulation of pleomorphic infiltrates of leukocytes. The etiology of these diseases is mainly unknown. CD45 is a hemopoietic cell specific tyrosine phosphatase essential for antigen receptor mediated signaling in lymphocytes and different patterns of CD45 splicing are associated with distinct functions. Recently a polymorphism (C77G) in exon 4 of CD45 causing abnormal CD45 splicing and a point mutation affecting CD45 dimerization were implicated in multiple sclerosis in humans and lymphoproliferation and autoimmunity in mice respectively. Here we show that two patients with HLH exhibited abnormal CD45 splicing caused by the C77G variant allele, while a further 21 HLH patients have normal CD45. We have also examined 62 LCH patients and found three to have the C77G mutation. Peripheral blood thymus-derived (T) CD8(+) cells from normal individuals carrying the C77G mutation show a significant decrease in the proportion of cells expressing L-selectin and increased frequency of cells with LFA-1(hi) expression. It remains to be established whether C77G is a contributing factor in these histiocytic disorders.